Status umetne inteligence v svetu umetnosti - Matjašič, Kristijan (Analiza: časopis za kritično misel, 2025)
The Status of Artificial Intelligence in the World of Art Today, we are witnessing a very rapid development of artificial intelligence (AI) in practically all fields. The most widely known or notable development in the field of AI is the development of ChatGPT by OpenAI. ChatGPT is a tool which answers questions, and helps in writing texts, essays, and programming code with the help of AI. However, in recent years, another form of creative AI has been brought closer to the public, which, however, does not deal with language, but is artistically involved in the field of visual and other arts. Probably the most famous AI software for creating or generating visual art is DALL-E, which, like ChatGPT, is owned by OpenAI. In the article, we will touch upon the “problem” of introducing AI into the art world and what AI art represents to society in contrast to “normal” human art. We will mainly be interested in questions such as what AI art is, whether AI art can even be considered art, whether AI can be an artist in itself or is just a tool, and how and why AI art affects art itself.